Separating two painting campaigns in Saul and David, attributed to Rembrandt, using macroscale reflectance and XRF imaging spectroscopies and microscale paint analysis - Dooley, Kathryn A.; Gifford, E. Melanie; van Loon, Annelies; Noble, Petria; Zeibel, Jason G.; Conover, Damon M.; Alfeld, Matthias; Van der Snickt, Geert; Legrand, Stijn; Janssens, Koen; Dik, Joris; Delaney, John K. (Heritage science, 2018)
Late paintings of Rembrandt van Rijn (1606–1669) offer intriguing problems for both art historians and conservation scientists. In the research presented here, the key question addressed is whether observed stylistic differences in paint handling can be correlated with material differences. In Saul and David , in the collection of the Royal Picture Gallery Mauritshuis in The Hague, NL, the stylistic differences between the loose brushwork of Saul’s cloak and the more detailed depiction of his turban and the figure of David have been associated with at least two painting stages since the late 1960s, but the attribution of each stage has been debated in the art historical literature. Stylistic evaluation of the paint handling in the two stages, based on magnified surface examination, is further described here. One of the research goals was to determine whether the stylistic differences could be further differentiated with macroscale and microscale methods of material analysis. To address this, selected areas of the painting having pronounced stylistic differences were investigated with two macroscopic chemical imaging methods, X-ray fluorescence and reflectance imaging spectroscopies. The pigments used were identified and their spatial distribution was mapped. The mapping results show that the passages rendered in more detail and associated stylistically with the first painting stage, such as the orange-red color of David’s garment or the Greek key design in Saul’s turban, were painted with predominately red ochre mixed with vermilion. The regions of loose, bold brushwork, such as the orange-red slashing strokes in the interior of Saul’s cloak, associated with the second painting stage, were painted with predominately red ochre without vermilion. These macroscale imaging results were confirmed and extended with scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM–EDX) analysis of three cross-sections taken from regions of stylistic differences associated with the two painting stages, including one sample each from the right and left sleeve of David, and one from the interior of Saul’s cloak. SEM–EDX also identified a trace component, barium sulfate, associated with the red ochre of the second stage revisions. Combining mapping information from two spectroscopic imaging methods with localized information from microscopic samples has clearly shown that the stylistic differences observed in the paint handling are affiliated with differences in the chemical composition of the paints.